The Relationship between Psychological Capital and Accessible Resources to Support the Organization Power's Sustainability in School Administrators at the Islamic Formal School Education Institute (Islamic Elementary School and Islamic Junior High School) - Mesiono Mesiono; Muamar Al Qadri; Ahmad Fuadi; Zaifatur Ridha (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aim of this study is to investigate the relationship between psychological capital and the resources available to enable organizational strong sustainability in a school administrator. Managers who employ and value the following sorts of power in institutions, particularly educational institutions: competency, appreciation, persuasive strength, legal force, and charismatic strength. It has an effect on the psychological well-being of teachers in school organizations, which has a bearing on performance and daily life. Within this context, research on the concept of psychological capital has been advanced and excelled. This study prioritizes optimism about ideas, expectations, psychological durability, and self-efficacy, all of which are qualities of psychological capital. The concept of psychological capital is gaining ground, and one may argue that it is strongly tied to organizational strength. After scanning and analyzing the literature on this subject, it can be concluded that the school administrator's power and manipulation of power in school organizations can have an effect on the dimensions of teachers' psychological capital such as optimism, expectations, psychological resistance, and self-efficacy.